Tindak Pidana Korupsi Dan Aktivitas Underground Economy - Aloysius Kristianto (Bina Ekonomi, 2019)
Special and continuous attention need to be paid to the phenomenon of underground economic activities, especially in deciding the determination of this economic activities to decrease, monitor, and prevent phenomena that are adverse to national/regional income. The aims of this study are to analyze the activities and the potential for corrupt behavior of the underground economic agents, looking to avoid the tax revenues and implications on interest prices from underground economic activities. The method used for this research is a Explanatory Sequential Mix Methods, first analyzed quantitatively by formulating an equation model and applied using the purposefully selected method. The findings of the study showed that corruptive behavior in the underground economic activities has a positive influence on the amount of money supplied in narrow terms (M1-currency) from the regional levels in the 3T (foremost-outermost-underdeveloped) region. Increased corruption levels can boost the amount of money circulating in society. During most of the higher tax collection, the supply of money will increase (M1). It is necessary to implement pentahelix elements to build a synergy between actors and to begin implementing and mastering electronic/digital systems with E-Government systems in every financial transaction.   Keywords: Underground economy; narrow money; tax on revenue; sequential explanatory methods; corruption